Efektivitas Penyelenggaraan Jaminan Sosial Ketenagakerjaan Pada PT Lamaison (LM) - Faikotul Masruchah; Ni Komang Arini Styawati ; I Made Arjaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article is to test the effectiveness of Law Number 24 of 2011 concerning Social Security Administering Bodies in PT Companies. LM and sanctions given to companies if they do not carry out the mandate of the Manpower Law. This research method uses an empirical method, namely a process that aims to interpret research data. The results of this research are that the implementation of Law Number 24 of 2011 concerning BPJS related to employment in furniture companies has not been effective. Sanctions imposed on companies that do not carry out the statutory mandate to provide their employees with social security are sanctions in the form of written warnings and fines.